From compliance to adherence and concordance, what quantitative and qualitative studies have synthesized? - Khuan, Lee; Chin , Yit Siew; Abdul Rahman, Hejar; Loong, Yik Yee (SAGE Publications, 2008)
Poor adherence has long been identified as the major health challenge in the prevention and treatment of chronic diseases. The purpose of the present study is to provide a critical review on the revolution of the “compliance” concepts from compliance to adherence and concordance to both pharmacological and non-pharmacological therapies. Hence, the present study attempts to provide an update of the possible factors related to adherence by incorporating findings from both qualitative and quantitative studies with respect to various chronic conditions regardless of their causes. A comprehensive literature search was performed using online databases from Library of University Putra Malaysia, and Pub Med based on the keywords. From the present studies, the findings showed that both quantitative and qualitative studies cannot be neglected in assessing adherence and its related problems. One of major findings from the present review is that “compliance” was no more suitable for current treatments and it is important to defined concepts of the terms used (adherence or concordance) correctly and clearly. The problems of definition or concepts of the terms used further affects the measurements and the results of the studies. It should be noted that the measurements and findings of the studies reviewed reflected that researchers placed great value on medication adherence, but have little attention to the non-pharmacological aspect of adherence. Since medications is not the only way of treatments for many chronic diseases and many patients resisted to take medications due to the strong negative image of medications, non-pharmacological treatments like lifestyle modifications seems to be more natural way of treatments. This may be one of the vital factor of why little progress of patients’ adherence to treatments throughout these three decades. There were three general factors related to adherence to treatments, namely socio-economic factor, treatments-related factor and disease-related factor. The findings showed that both qualitative and quantitative studies found consistent results for most of the factors, except the experience of diseases symptoms. Factors identified in the qualitative studies provides a better understanding on patients’ adherence to treatments regardless of illnesses, but more quantitative studies with a representative sample and valid instruments are in need to clarify these factors. Both study designs contribute important values to the adherence studies. Hence, it is suggested that future studies should not only consider qualitative study but also quantitative studies.